Croisements et échanges nord-africains : Abderrahmane Bouguermouh et « l’espace cinématographique » amazigh/berbère - Daniela Merolla (L’Année du Maghreb)
This article proposes using the notion of the “Amazigh/Berber cinematic space” (Merolla, 2006, 2019) to explore linguistic, artistic, and cultural exchanges and intersections that remain under-studied in analyses of North African cinema. It focuses on the cinematic work of Abderrahmane Bouguermouh, one of the first filmmakers to create films in Amazigh/Berber (Kabyle), and analyses his short film La Grive in Arabic and French and his now-lost medium-length film Comme une âme in the Kabyle language. I aim to contribute to a deeper understanding of Amazigh/Berber film production, drawing on recent research by scholars such as Armes, Austin, Brahimi, Devaux Yahi, Lafer, Higbee, and others. Following this, I examine the challenges that filmmakers like Bouguermouh have encountered in producing films in Amazigh and other languages. This analysis will help identify the characteristics and continuities of the “Amazigh/Berber cinematographic space” in relation to broader cinematic definitions, including postcolonial, diasporic, transnational, and accented cinema, as well as cinéma-monde, and cinema of transvergence.